10‐Gingerol alleviates hypoxia/reoxygenation‐induced cardiomyocyte injury through inhibition of the Wnt5a/Frizzled‐2 pathway. Issue 7 (5th June 2021) - Zheng, Bin; Qi, Jiaying; Liu, Panpan; Zhang, Muqing; Zhang, Yuanyuan; Xue, Yucong; Han, Xue; Xu, Shan; Chu, Li
Abstract: 10‐Gingerol (10‐Gin), an active ingredient extracted from ginger, has been reported to have beneficial effects on the cardiovascular system. However, 10‐Gin has not been proved to offer protection against cardiomyocyte injury induced by hypoxia/reoxygenation (H/R). This study aimed to investigate the protective effects of 10‐Gin against H/R‐induced injury and its potential mechanisms in cardiomyocytes. A H/R injury model of H9c2 cardiomyocytes was established using 600 μmol/L CoCl2 to induce hypoxia in the cells for 24 hr and then reoxygenated for 3 hr. 10‐Gin was pretreated with H9c2 cardiomyocytes for 24 hr to assess its cardiomyocyte protection. Our results showed that 10‐Gin improved the viability of H9c2 cardiomyocytes in the H/R model and decreased the activities of creatine kinase, lactate dehydrogenase, and the generation of reactive oxygen species. By intracellular Ca 2+ ([Ca 2+ ]i ) fluorescence, we found that 10‐Gin could significantly reduce the [Ca 2+ ]i concentration. 10‐Gin administration increased the activities of antioxidase and reduced malondialdehyde content and inflammatory cytokine levels. 10‐Gin also reduced the apoptosis levels. Importantly, 10‐Gin administration decreased the gene and protein expressions of Wnt5a and Frizzled‐2. In conclusion, 10‐Gin alleviates H/R‐induced cardiomyocyte injury, which is associated with the antioxidation, anti‐inflammation, antiapoptosis action, and reduction of [Ca 2+ ]i overload by suppressing the Wnt5a/Frizzled‐2 pathway. Abstract : 10‐Gingerol can attenuate the injury caused by hypoxia /reoxygenation reduce oxidative stress, Ca2+ overload, inflammation, and apoptosis, which is related to the inhibition of the Wnt5a/Frizzled‐2 pathway. Our research provides an experimental basis and new treatment strategies for MIRI. However, further research will be needed before these treatments can be used in clinics.